Comparison of the Efficacy and Safety of Early Rule-Out Pathways for Acute Myocardial Infarction. Issue 17 (25th April 2017) - Chapman, Andrew R.; Anand, Atul; Boeddinghaus, Jasper; Ferry, Amy V.; Sandeman, Dennis; Adamson, Philip D.; Andrews, Jack; Tan, Stephanie; Cheng, Sheun F.; D'Souza, Michelle; Orme, Kate; Strachan, Fiona E.; et al.
Abstract : Background: High-sensitivity cardiac troponin assays enable myocardial infarction to be ruled out earlier, but the optimal approach is uncertain. We compared the European Society of Cardiology rule-out pathway with a pathway that incorporates lower cardiac troponin concentrations to risk stratify patients. Methods: Patients with suspected acute coronary syndrome (n=1218) underwent high-sensitivity cardiac troponin I measurement at presentation and 3 and 6 or 12 hours. We compared the European Society of Cardiology pathway (<99th centile at presentation or at 3 hours if symptoms <6 hours) with a pathway developed in the High-STEACS study (High-Sensitivity Troponin in the Evaluation of Patients With Acute Coronary S yndrome) population (<5 ng/L at presentation or change <3 ng/L and <99th centile at 3 hours). The primary outcome was a comparison of the negative predictive value of both pathways for index type 1 myocardial infarction or type 1 myocardial infarction or cardiac death at 30 days. We evaluated the primary outcome in prespecified subgroups stratified by age, sex, time of symptom onset, and known ischemic heart disease. Results: The primary outcome occurred in 15.7% (191 of 1218) patients. In those less than the 99th centile at presentation, the European Society of Cardiology pathway ruled out myocardial infarction in 28.1% (342 of 1218) and 78.9% (961 of 1218) at presentation and 3 hours, respectively, missing 18 index and two 30-day events (negative predictive value, 97.9%; 95% confidence interval, 96.9–98.7). The High-STEACS pathway ruled out 40.7% (496 of 1218) and 74.2% (904 of 1218) at presentation and 3 hours, missing 2 index and two 30-day events (negative predictive value, 99.5%; 95% confidence interval, 99.0–99.9; P <0.001 for comparison). The negative predictive value of the High-STEACS pathway was greater than the European Society of Cardiology pathway overall ( P <0.001) and in all subgroups, including those presenting early or known to have ischemic heart disease. Conclusions: Use of the High-STEACS pathway incorporating low high-sensitivity cardiac troponin concentrations rules out myocardial infarction in more patients at presentation and misses 5-fold fewer index myocardial infarctions than guideline-approved pathways based exclusively on the 99th centile. Clinical Trial Registration: URL:http://clinicaltrials.gov . Unique identifier: NCT01852123. Abstract : Supplemental Digital Content is available in the text.